Needs Assesment Buklet Edukatif Tematik Integratif untuk Memberikan Pendidikan Kesehatan Reproduksi bagi Peserta Didik Kelas Atas di Sekolah Dasar - Sunarni Sunarni; Raden Bambang Sumarsono; Desi Eri Kusumaningrum; Dedi Prestiadi (Universitas Negeri Malang, 2022)
Abstract: The research objectives are: 1) conducting a needs assessment and 2) designing the development of an integrative thematic educational booklet and guidelines for its use. The research uses a descriptive quantitative approach. The research was conducted at